Z γ production and limits on anomalous ZZ γ and Z γγ couplings in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Askew, A.; et al. (American Physical Society (APS), 2012)
We present a measurement of pp̄→Zγ→δ +δ -γ (δ=e, μ) production with a data sample corresponding to an integrated luminosity of 6.2fb -1 collected by the D0 detector at the Fermilab Tevatron pp̄ Collider. The results of the electron and muon channels are combined, and we measure the total production cross section and the differential cross section dσ/dpTγ, where pTγ is the momentum of the photon in the plane transverse to the beam line. The results obtained are consistent with the standard model predictions from next-to-leading order calculations. We use the transverse momentum spectrum of the photon to place limits on anomalous ZZγ and Zγγ couplings. © 2012 American Physical Society.